The Effect of Locus of Internal Control on The Ability to Maintain a MicroBusiness in The Pandemic Time Covid-19: Pengaruh Locus of Internal Control terhadap Kemampuan Mempertahankan Bisnis Wirausaha Mikro di Masa Pandemi Covid-19 - Muharika Dewi; Riri Putri Dika; Vivi Puspita Sari (Perkumpulan Doktor Indonesia Maju, 2020)
Maintaining business in times of multidimensional crisis due to the COVID 19 pandemic is something that is difficult for micro-entrepreneurs to do. The character of entrepreneurs affects every decision that must be made in a situation full of uncertainty. This paper reveals the relationship between locus if internal control (LoC) characteristics and the ability to sustain micro-entrepreneurial ventures. Research with a quantitative approach, the data were analyzed descriptively and associatively using the Pearson correlation formula, and contribution analysis. The instrument uses a questionnaire, the sample is entrepreneurs with the strength of micro-scale capital taken by random sampling using incidental sampling techniques through google form data collection. The analysis shows that the micro-entrepreneurial business conditions at a score of 63.8% are categorized as bad, while LoC has a score of 58.4% in the bad category, the correlation results have a positive direction of 0.726, the value of X's contribution to Y is 52.6%.